IMPACT OF THE WORLD PRICES ON THE NATIONAL PRICING SYSTEM - Yuri A. Sarukhanyan (Вестник Российского экономического университета имени Г. В. Плеханова)
In article the main directions of influence of the world prices for the Russian system of the prices are investigated: first, it is the prerequisites connected with functioning of the global markets; secondly, it is factors to which tactical tendencies in world economy are carried; thirdly, it is channels of manifestation and distribution which are connected with upward and bearish dynamics of the export prices of national producers, growth or decrease in import prices; fourthly, it is the regularities of macroeconomic regulation connected with increase in value of exchange prices, strengthening of influence of dynamics of exchange rates, monetary policy at price dynamics of the world commodity markets. Key tendencies of influence of the world prices at the present stage, alignments of the exchange and foreign trade prices, interrelations of the national and world prices for separate goods for the markets depending on external demand, dependence between currency policy of the states, dynamics of the balance of payments and strengthening of competitive advantages in the external markets are revealed. Conclusions of work can be used when developing fundamentals of monetary and credit and budgetary policy of the state for the medium term.